Genetic Associations with 25-Hydroxyvitamin D Deficiency in HIV-1-Infected Youth: Fine-Mapping for the GC/DBP Gene That Encodes the Vitamin D-Binding Protein - Porter, Travis; Li, Xuelin; Stephensen, Charles B.; Mulligan, Kathleen; Rutledge, Brandy; Flynn, Patricia N.; Lujan-Zilbermann, Jorge; Hazra, Rohan; Wilson, Craig M.; Havens, Peter L.; Tang, Jianming (Frontiers in Genetics, 2013)
Serum 25-hydroxyvitamin D [25(OH)D] is often deficient (